DIGITAL INFLUENCERS AS KNOWLEDGE FACILITATORS: EXAMINING THE IMPACT OF GERALD VINCENT’S CONTENT - Prasetyo, Kurniawan; Irfan, Muhammad Esya; Bate, Andi Pajolloi; Iqbal, Muhamad (ASPIRATION Journal, 2025)
The advancement of digital media has driven social media and influencer figures into key information providers that are increasingly relied on by the public, especially the youth generation.  This study aims to analyze how Gerald Vincent’s social media content (@GeraldVincentt), fulfills the informational needs of his followers and contributes to digital literacy. This study used a quantitative approach through survey of 100 active followers of Gerald Vincent on Instagram and TikTok platforms, employing correlation analysis and simple linear regression. The results indicate a moderate to strong positive correlation between audience engagement with social media content and information fulfillment (r = 0.609). Regression analysis confirms that Gerald Vincent’s content significantly enhances knowledge acquisition among his followers (43.1%). This study concludes that a social media influencer has the potential to play a role as a knowledge facilitator, but still requires concern regarding  the credibility aspect and accuracy of information in knowledge dissemination in digital media.